Sociodemographic and epidemiological profile of leprosy patients in an endemic region in Brazil - Martins, Ronald Jefferson [UNESP]; Oliveira Gomes Carloni, Maria Emilia [UNESP]; Saliba Moimaz, Suzely Adas [UNESP]; Saliba Garbin, Clea Adas [UNESP]; Garbin, Artenio Jose Isper [UNESP] (Soc Brasileira Medicina Tropical, 2016)
Introduction: The incidence of Hansen's disease is high in overlooked populations. Methods: Data of Hansen's disease cases reported in the information system of the Department of Informatics, Brazilian Unified Health System, from 2013 to 2014 were analyzed. Results: Among 434 studied cases of Hansen's disease, the female sex (52.5%), adult age (73.7%), low educational level (61.8%), and multibacillary form were associated with higher prevalence rates. Conclusions: Hansen's disease is more frequent among female adults with a low educational level, and the prevalence of multibacillary leprosy reflects disease detection at late stages.
Keywords: Health profile; Socioeconomic factors; Hansen's disease